Pengaruh Ukuran Partikel Pada Pembuatan Briket Arang Lumpur IPAL Pabrik Sawit Dan Cangkang Biji Karet - Mutia Khairunnisa; Elvi Yenie; Ivnaini Andesgur (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The utilization of fossil energy sources overload resulted in the availability of energy sources depleting and should be offset by the provision of alternative energy renewable, abundant amount, and the cost price is so affordable by the public, one of which is briquette. Palm oil mill sludge is one of the wastes at the palm oil processing. Palm oil smill sludge with the addition of rubber seed shells can be used as raw material for making briquettes through the carbonization process. This study aims to study the effect of particle size variations on the proximate analysis of the briquettes produced. Variations of particle size were 60, 80, and 100 mesh with the composition of palm oil mill sludge and rubber seed shells were 60%:40%. The results showed that the best briquettes were obtained at 100 mesh particle size with 4% moisture content, 4.5% ash content, 9.3% volatile matter and 82.2% fixed carbon.Keywords: briquettes, carbonization, rubber seed shell, palm oil mill sludge